Identification of SMYD2 interactions and substrates by immunoprecipitation coupled to mass spectrometry - Abu-Farha, Mohamed (University of Ottawa (Canada), 2011)
Very little is known about SMYD2 (SET and MYND containing protein 2), which is a member of the SMYD protein family. However, the interest in better understanding the roles of SMYD2 has grown due to recent reports indicating that SMYD2 methylates p53 and histone H3. I report the cytosolic and nuclear interactome of SMYD2 using a combination of IP-HTMS, ChIP-HTMS and co-immunoprecipitation methods. In particular, I report that SMYD2 interacts with HSP90alpha independently of the SET and MYND domain. The interaction of SMYD2 with HSP90alpha enhances SMYD2 histone methyltransferase activity and specificity for histone H3 at lysine 4 (H3K4) in vitro. Interestingly, histone H3K36 methyltransferase activity is independent of its interaction with HSP90alpha similar to LSD1 dependency on the androgen receptor. I also show that HSP90alpha is methylated by SMYD2 at lysine 209 and 565. Methylation of HSP90alpha is removed by LSD1. We have demonstrated that SMYD2 is being automethylated. Automethylation of SMYD2 is inhibited by the increasing concentration of recombinant SMYD2 in vitro. Even though the function of SMYD2 is still not fully understood, it is clear that it acts as an activator of gene expression as shown by microarray analysis. In this experiment, I have showed using a cDNA microarray that SMYD2 gain of function is correlated with the up-regulation of 37 and down-regulation of 4 genes. The majority of these genes are involved in the cell cycle, chromatin remodeling, and transcriptional regulation. TACC2 is one of the genes up regulated as a result of SMYD2 gain of function. Up-regulation of TACC2 by SMYD2 occurs as a result of SMYD2 binding to the TACC2 promoter where it methylates H3K4. When combined together, the interaction and the gene expression data confirm the suggested role of SMYD2 in DNA damage response.
Keywords: Chemistry, Biochemistry.